Cross‐Border Reproductive Care: Two Lenses in Political Science. Issue 4 (21st November 2018) - Stapleton, Patricia; Skinner, Daniel
Abstract : Cross‐border reproductive care (CBRC)—when patients travel outside their country to seek assisted reproductive services—is a booming industry. Globalization facilitates the increase in CBRC by reducing transportation costs, removing language barriers, and liberalizing the reproductive services market. Yet global and domestic regulatory responses are failing to keep pace, raising ethical, economic, political, and social issues. Political science has been slow to contribute to our understanding of CBRC politics and policies. This article first establishes the gap in existing CBRC research, before presenting how political scientists can respond in two specific areas: 1) the role of globalization health governance in relation to CBRC and 2) the political implications and potentials of "medical necessity" in shaping patient motivations for seeking—as well as their ultimate access to—CBRC. New research in these areas will aid policymakers in recognizing the context in which they must develop CBRC regulations.